A PCM Thermal Storage for Ground-source Heat Pumps: Simulating the System Performance via CFD Approach. (November 2016) - Bonamente, Emanuele; Aquino, Andrea; Cotana, Franco
Abstract: The conventional design of ground source heat pumps (GSHPs) is based on the peak heating and cooling loads. A possible optimization in GSHP design, including a thermal storage device between the ground exchangers and the heat pump, was already realized and it was found that a reduced-size geothermal field (-66%) is still able to cover the energy demand. In this paper, the design of the prototype was used as a starting point to study the potentialities of two possible upgrades for the optimization of the energy performance (COP) of the system. In the first case, the thermal storing material is water, as in the working prototype, and the efficiency is improved removing the cylindrical heat exchangers that were designed to separate the ground side from the heat pump side. In the second case, a completely new and more compact thermal storage was designed using phase change materials (PCMs). Computational fluid dynamics (CFD) simulations were performed in a transient regime to validate the model against observed data and to assess the potentiality of the two improvements. The system behavior is studied in terms of driving energy input and output energy production. Significant improvements of the system COP are observed (up to +20%). In the first case (water thermal storage), the overall COP is 4.1 during winter and 5.7 during summer, in the second case (PCM thermal storage), the COP is 4.1 and 5.9, respectively. The PCM thermal storage, in particular, is approximately 10 times smaller than the original design, and could be easily placed within the technical room.